2018
DOI: 10.1039/c7ra12529a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the global metabolic profile of liquiritin in rat plasma, urine, bile and feces based on UHPLC-FT-ICR MS

Abstract: Liquiritin is a major flavonoid in Radix Glycyrrhizae and it has been reported to possess various pharmacological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Literature on the biotransformation of isoliquiritigenin and liquiritigenin have been reported previously. Briefly, β-glucosidase hydrolyzes liquiritin in the intestinal flora, and liquiritigenin is absorbed from the jejunum to the colon and conjugated with UDPGA and sulfate or methylated to produce liquiritigenin-glucuronide and sulfoconjugates or methylconjugates in the gut wall enzymes and in the liver (Németh et al 2003;Zhang et al 2016; www.journal-dtt.org Ma et al 2018). Additionally, isoliquiritigenin is biosynthetically and structurally interrelated to liquiritigenin (Simmler et al 2013;Choi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the biotransformation of isoliquiritigenin and liquiritigenin have been reported previously. Briefly, β-glucosidase hydrolyzes liquiritin in the intestinal flora, and liquiritigenin is absorbed from the jejunum to the colon and conjugated with UDPGA and sulfate or methylated to produce liquiritigenin-glucuronide and sulfoconjugates or methylconjugates in the gut wall enzymes and in the liver (Németh et al 2003;Zhang et al 2016; www.journal-dtt.org Ma et al 2018). Additionally, isoliquiritigenin is biosynthetically and structurally interrelated to liquiritigenin (Simmler et al 2013;Choi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the metabolites of LQ in healthy rats, M2, M7, and M10 have been found in healthy rat metabolic models. Moreover, nine new LQ metabolites were discovered in the study of LQ metabolites (Jiang et al, 2021; Zhang et al, 2020; Zhang, Xu, & Zhan, 2018; Ma et al, 2018). Different from previous studies on the LQ metabolic pathway in healthy rats, this study found a new phase II metabolic pathway of LQ binding to amino acids in the AMI rat model.…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro metabolism studies, LQ exerts an important influence on human intestinal bacteria growth (Zhang et al, 2014). Previous studies on LQ metabolism have shown that sulfation, glucosylation, methylation, hydroxylation, and acetylation are the main pathways of LQ metabolism in healthy rat plasma (Jiang et al, 2021;Zhang et al, 2020;Zhang, Liang, et al, 2018;Ma et al, 2018). Research efforts have been made in LQ metabolism study but have not yet explored the metabolism and distribution in pathological state, which might be different in healthy rats (Jin et al, 2016).…”
mentioning
confidence: 99%